The Influence of Peer Relationships on the Social Development of Children with Autism Spectrum Disorder - Karna, Wioleta; Stefaniuk, Ireneusz (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: Peer relationships significantly impact the social development of children with Autism Spectrum Disorder (ASD), influencing their emotional well-being, academic performance, and overall quality of life. This study aims to explore the influence of peer relationships on the social development of children with ASD, identifying the challenges they face and the support systems that facilitate positive social outcomes.Methodology: This qualitative study involved 23 participants, including ten children with ASD, ten parents, and three teachers and support staff. Data were collected through semi-structured interviews and analyzed using NVivo software. Thematic analysis was conducted to identify recurring themes, and theoretical saturation was achieved to ensure comprehensive data coverage.Findings: The analysis revealed four main themes: Social Interaction Challenges, Peer Relationship Dynamics, Parental and Teacher Support, and Positive Outcomes. Social Interaction Challenges included difficulties in communication, sensory overload, social anxiety, and misinterpretation of social cues. Peer Relationship Dynamics covered forming and sustaining friendships, inclusion and exclusion, and the influence of peers. Parental and Teacher Support highlighted strategies for social development, the role of teachers, parental involvement, and community resources. Positive Outcomes encompassed improvement in social skills, building self-esteem, increased independence, and enhanced academic performance.Conclusion: Peer relationships play a crucial role in the social development of children with ASD. Despite significant challenges, targeted interventions and supportive environments can lead to substantial improvements in social competencies. The findings underscore the importance of inclusive settings, peer-mediated interventions, and active involvement of parents and teachers in fostering positive social interactions for children with ASD.